MARKETING FOR A SUSTAINABLE WORLD: REDUCING WASTE WITH PRODUCT ANTHROPOMORPHISM - AHMED ASHHAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Brand anthropomorphism refers to the tendency to attribute human-like characteristics and behaviors to non-human objects, a practice widely used in marketing to enhance consumer engagement. This approach, seen in strategies like brand ambassadors, human-like product designs, or brand characters, helps foster emotional connections between consumers and brands, resulting in positive outcomes like increased brand liking, loyalty, and consumer behavior. Additionally, the concept of the IKEA effect, where consumers value products they’ve personally interacted with or customized, further supports the idea that anthropomorphized products, through the psychological effort they require, can deepen consumer attachment and increase product longevity. In this paper, we argue that by applying the strategies developed for brand anthropomorphism to products, we can enhance the bond consumers feel towards their products, thereby potentially encourage more sustainable consumption practices by reducing the likelihood of product disposal.